Limited war in South Asia - Gates, Scott, author.
1 online resource (227 pages)
Keywords: "This book examines the origins, courses, and consequences of conventional wars in post-colonial South Asia. Although South Asia has experienced large-scale conventional warfare on several occasions since the end of World War II, there is an almost total neglect of analysis of conventional warfare in the Indian subcontinent. Focusing on China, India and Pakistan, this volume, therefore, takes a unique approach. Regional rivalries between India and Pakistan are linked with global rivalries between the USA and USSR (later Russia) and then China, and war is defined in a broader perspective. The book analyses the conduct of land, sea and air warfare, as well as the causes and consequences of conflicts. Tactical conduct of warfare (the nature of mobile armoured strikes and static linear infantry combat supported by heavy artillery) and generalship are studied along with military strategy, doctrine, and grand strategy (national security policy) which is an amalgam of diplomacy, military strategy and economic policy. While following a realpolitik approach, this book blends the development of military strategies and doctrines with the religious and cultural ethos of the subcontinent's inhabitants. Drawing on sources not easily accessible to Western scholars, the overall argument put forward by this work is that conventional warfare has been limited in South Asia from the very beginning for reasons both cultural and realpolitik. This book will be of much interest to students of South Asian politics, security studies, war and conflict studies, military studies and IR in general."--Provided by publisher.